Modernization of the state tax service on the example of the taxpayer's electronic cabinet - Chernelevsky, Leonid; Diomina, Maria (My University, 2020)
This article discusses filing tax returns electronically. The modem way such as the electronic office of the taxpayer is given. The development of the State Tax Service of Ukraine at all stages of modernization is considered and it is determined that today informatization is a priority direction of the department’s development. It is revealed that the modernization of tax department processes with the participation of innovations and information technologies, development of the e-taxation direction, is primarily aimed at improving the efficiency of the MRF. For three years, Ukraine has undergone a rather radical reform of both the tax system and tax policy in particular. Tax policy is a combination of forms and methods of taxation of both the state and taxpayers. If the reform of the tax system is carried out by changing the tax rates, expanding the tax base, abolishing some taxes and introducing other taxes, then reforming the tax policy will change the forms and methods of the state in the sphere of taxation. One of the elements that the state is constantly trying to change in order to comply with taxpayer tax discipline is the form of filing tax returns. This relates to the filing electronic tax returns. The importance of research in this area is evidenced by the rapid development of the information economy, which takes into account the potential of information technology. In particular, the modernization of information and communication technologies (hereinafter — ICT) by governmental structures has ended on the path of democratization of public administration. There is no doubt about the urgency of this issue as the use of ICT in the public sector creates new mechanisms in the context of building an effective, responsible, accountable and transparent governance. Due to the results of the conducted research, it should be noted that the modernization of the state tax service in the field of automation of the processes of tax administration, informatization and development of information infrastructure was not the subject of separate scientific research. У статті розглянуто подання податкової звітності в електронній формі. Наведено сучасний спосіб — електронний кабінет платника податків. Проаналізовано розвиток Державної податкової служби (ЦПС) України на всіх етапах модернізації та визначено, що на сьогодні інформатизація є пріоритетним напрямком розвитку. Виявлено, що модернізація процесів податкового департаменту за участю інновацій та інформаційних технологій, розвитку безпосередньо електронного оподаткування передусім спрямована на підвищення ефективності ДПС. Протягом трьох років Україна переживає досить радикальну реформу як податкової системи, так і податкової політики зокрема. Податкова політика — це поєднання форм і методів оподаткування як держави, так і платників податків. Якщо реформа податкової системи здійснюється шляхом зміни ставок оподаткування, розширення бази оподаткування, скасування деяких податків і запровадження інших податків, то реформування податкової політики змінить форми і методи держави у сфері оподаткування. Одним з елементів, які держава постійно намагається змінити, щоб виконати податкову дисципліну з боку платників податків, є форма подання податкових звітів. Це більше стосується подання електронної податкової звітності. Про важливість досліджень у цій галузі свідчить швидкий розвиток інформаційної економіки, яка враховує потенціал інформаційних технологій. Тож актуальність цього питання не викликає сумнівів, оскільки використання інформаційно-комунікаційні технології (ІКТ) у державному секторі створює нові механізми в контексті побудови ефективного, відповідального, підзвітного та прозорого державного управління. Слід зазначити, що модернізація державної податкової служби у сфері автоматизації процесів податкового адміністрування, інформатизації та розвитку інформаційної інфраструктури не була предметом окремого наукового дослідження.
Keywords: state tax administration; taxation; tax policy; electronic tax reporting; modernization; оподаткування; податкова політика; електронна податкова звітність; модернізація; державне податкове управління; кафедра обліку і аудиту